The great divide - Dodds, Dayle Ann.; Mitchell, Tracy (Cambridge, MA : Candlewick Press, 1999)
Eighty people begin to race in the Great Divide, but each new challenge divides the number of racers in half.
Keywords: Racing -- Fiction; Division -- Fiction; Stories in rhyme